Raymond Damadian: revolutionizing Medicine with magnetic resonance imaging - Cedeño, Lahelya N.; Vélez, Valeria A.; Robles, Jaime A.; Reina, Juan D.; Saltos, Magno A. (Revista Gregoriana de Ciencias de la Salud, 2024)
This essay examines the groundbreaking contribution of Raymond Vahan Damadian to the development of magnetic resonance imaging (MRI), a technology that transformed diagnostic medicine. Damadian, recognized as the inventor of the first MRI scanner, demonstrated in 1971 that this technique could be used to detect diseases such as cancer, marking a milestone in medical history. His early research in tissue characterization through MRI propelled the design of advanced equipment, essential for modern clinical practice. This work highlights not only his technical impact but also the cultural and scientific influence of MRI in understanding the human body and detecting pathologies, cementing his legacy in the evolution of medical thought. Despite some controversies, such as the omission of certain scientists from the Nobel Prize, the contributions of the pioneers of this technology have been widely recognized, solidifying their place in the history of Medicine.